Evaluating the economic impact of Southern Africa’s public policy response to the management of covid-19 - Ditsela, Mokome Sabrina (Stellenbosch : Stellenbosch University, 2025)
ENGLISH SUMMARY: The COVID-19 pandemic has led many countries to implement strict lockdown measures to safeguard public health. Public policy responses are crucial for mitigating its effects on different sectors and communities. However, there is no size-fits-all approach to managing the pandemic. Southern African countries applied localised responses to the pandemic with lockdowns of varying intensity. The impact has been far-reaching. This study evaluates the economic impact of COVID-19 containment measures on selected countries in Southern Africa, namely South Africa, Botswana, Zimbabwe, and Zambia. This study adopted a comparative case study design to compare the COVID-19 response measures and economic impacts of the four cases. A desktop approach reviewed the available qualitative data to reflect the economic impact of key indicators such as GDP, unemployment, poverty, and inflation. The pandemic and lockdowns had a profound and adverse economic impact. This exacerbated the pre-existing structural challenges in the economy, which offered sluggish economic growth, high unemployment rates and poverty. The findings indicate that the COVID-19 pandemic and lockdown significantly affected the economies of South Africa, Botswana, Zimbabwe, and Zambia. There was a significant decline in GDP, employment, poverty, and an increase in inflation. South Africa's GDP growth in 2019 was 0.2%, but the real GDP growth for 2020 was revised to minus 8.2%, with sectors such as construction, manufacturing, and retail bearing the hardest impact. Botswana's GDP decreased by 7.9% in 2020, the sharpest decline since the Great Recession. The hard-hit sectors included tourism and mining, which resulted in a massive decline in the export of goods. Zimbabwe's GDP contraction and recession in 25 years were exacerbated by the pandemic, resulting in a minus 4.5% GDP growth for 2020. This contraction resulted from the shutdown of economic activities, disruption of trade and production, increased debt, and exacerbation of existing structural inequalities. Zambia's economy also experienced a 4.0% decline in 2020 as a result of unparalleled deterioration across all major sectors of the economy as a result of disruption in supply chains, business closures, travel bans, and lower consumer spending. The lockdown effectively contained the virus, but border closures, restrictions on trade, and disruption in cross-border value chains and trade negatively affected the economies of Southern African countries. The COVID-19 pandemic has significantly worsened economic constraints in the region, resulting in an immediate contraction of GDP and increased unemployment, poverty, and inflation. Based on the findings, the thesis offers recommendations to improve the management of future economic lockdowns should a similar situation arise. Key recommendations include economic diversification to decrease the impact on overall GDP in sectors most vulnerable to trade and movement restrictions, improved economic infrastructure to enable the economy to continue activities regardless of shifts in modalities, and the support of diverse working methods that enable business continuity. To support community resilience, there is a need to revitalize small and medium-sized enterprises, invest in skill development, and improve social nets to address poverty. Furthermore, the COVID-19 pandemic has demonstrated that governments should try to avoid chaotic and poorly coordinated responses, increase regional and international collaboration, and establish clear and transparent communication channels.